2005
DOI: 10.1242/jcs.02565
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of focal adhesion dynamics and disassembly by phosphorylation of FAK at tyrosine 397

Abstract: One of the major tyrosine phosphorylation activities linked to integrin signalling is that of focal adhesion kinase (FAK). High amounts of FAK are located at specialised subcellular compartments known as focal adhesions. FAK tyrosine phosphorylation at focal adhesions is increased by various stimuli including integrin engagement during migration processes, growth factors and oncogene transformation. Phosphorylation of FAK at various tyrosine residues regulates focal adhesion turnover by mechanisms that are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
215
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(245 citation statements)
references
References 45 publications
20
215
0
3
Order By: Relevance
“…These findings seem to indicate that FAK Tyr 407 phosphorylation might inhibit the access of additional phosphates on Tyr 397 , perhaps because of increased negative charge repulsion. It has been known that FAK molecules phosphorylated at Tyr 397 reside close to the plasma membrane (21,22), and the absence of Tyr 397 phosphorylation decreases its residency at focal adhesions but not in cytosol (22). Consistent with this notion, higher levels of Tyr 407 phosphorylation were observed in cytosolic FAK versus membrane-bound FAK (Fig.…”
Section: Fak Tyrsupporting
confidence: 77%
“…These findings seem to indicate that FAK Tyr 407 phosphorylation might inhibit the access of additional phosphates on Tyr 397 , perhaps because of increased negative charge repulsion. It has been known that FAK molecules phosphorylated at Tyr 397 reside close to the plasma membrane (21,22), and the absence of Tyr 397 phosphorylation decreases its residency at focal adhesions but not in cytosol (22). Consistent with this notion, higher levels of Tyr 407 phosphorylation were observed in cytosolic FAK versus membrane-bound FAK (Fig.…”
Section: Fak Tyrsupporting
confidence: 77%
“…Nevertheless, impairment of cell motility in FRNK-expressing cells is apparently accompanied by increased focal contact formation in membrane ruffles thus suggesting that FRNK could still recruit other signalling or effectors proteins required for assembly of focal adhesion sites, and that decreased motility is due to impaired focal adhesion turnover rather than to weakened adhesion assembly. A role of FAK in cell movement acting preferentially in focal adhesion turnover rather than in initial formation has been previously suggested (Schlaepfer et al, 2004), and phosphorylation of both FAK and paxillin contributes to turnover of focal contacts (Turner, 2000;Brunton et al, 2005;Hamadi et al, 2005). Possibly, the decreased cell motility caused by inhibition of FAK expression or activity in HNSCC-derived cells is due to a decreased FAK phosphorylation and FAK-induced paxillin phosphorylation and, consequently, impaired focal adhesion turnover.…”
Section: Discussionmentioning
confidence: 92%
“…We recently reported that SLK is required for microtubule-dependent focal adhesion turnover during cell migration (Wagner et al, 2008). To investigate whether SLK plays a role in focal adhesion dynamics downstream of Neu activation, NMuMG cells expressing the various Neu mutants were infected with GFP control or kinase- The level of FAK phosphorylation at tyrosine 397 has been shown to correlate with adhesion turnover, as high levels are indicative of stable adhesions (Cook et al, 1998;Palazzo et al, 2001;Webb et al, 2002;Hamadi et al, 2005). We first evaluated the levels of phospho-FAK-Y397 in NeuNT-or NYPD-expressing cells after infection with a dominant-negative SLK.…”
Section: Neu-slk Signaling Induces Focal Adhesion Turnovermentioning
confidence: 99%
“…Cell motility is a dynamic process that requires the turnover of these structures. Growing evidence suggests that FAK autophosphorylation at Tyr 397 is important to signal turnover (Hamadi et al, 2005) by a src-dependent mechanism (Frame, 2004). Indeed, high levels of FAK-Y397 appear to correlate with stable adhesions and decreased motility (Palazzo et al, 2001;Palazzo and Gundersen, 2002).…”
Section: Erbb2-mediated Cell Migration Requires Slk K Roovers Et Almentioning
confidence: 99%